2015
DOI: 10.1111/ejn.12880
|View full text |Cite
|
Sign up to set email alerts
|

d‐amino acid oxidase knockout (Dao−/−) mice show enhanced short‐term memory performance and heightened anxiety, but no sleep or circadian rhythm disruption

Abstract: d‐amino acid oxidase (DAO, DAAO) is an enzyme that degrades d‐serine, the primary endogenous co‐agonist of the synaptic N‐methyl‐d‐aspartate receptor. Convergent evidence implicates DAO in the pathophysiology and potential treatment of schizophrenia. To better understand the functional role of DAO, we characterized the behaviour of the first genetically engineered Dao knockout (Dao−/−) mouse. Our primary objective was to assess both spatial and non‐spatial short‐term memory performance. Relative to wildtype (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 96 publications
(158 reference statements)
1
27
0
Order By: Relevance
“…Importantly, post hoc analysis suggested that such an effect was mostly driven by female mice. While future studies will be necessary to better understand why that might be the case, our observations add additional evidence to the growing body of literature showing a strong sex‐dependence of DAAO actions in the rodent brain (Labrie et al, ; Pritchett et al, ), as well as sex‐related differences in its expression levels in humans (Jagannath et al, ). Moreover, our results indicating that female mice are more sensitive than males to the disruption of D‐serine actions in the brain, are well aligned with previous reports showing the inability of DAAO to prevent the facilitatory actions of exogenously applied D‐serine on LTD (Zhang et al, ) or LTP (Yang et al, ) in male rodents.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Importantly, post hoc analysis suggested that such an effect was mostly driven by female mice. While future studies will be necessary to better understand why that might be the case, our observations add additional evidence to the growing body of literature showing a strong sex‐dependence of DAAO actions in the rodent brain (Labrie et al, ; Pritchett et al, ), as well as sex‐related differences in its expression levels in humans (Jagannath et al, ). Moreover, our results indicating that female mice are more sensitive than males to the disruption of D‐serine actions in the brain, are well aligned with previous reports showing the inability of DAAO to prevent the facilitatory actions of exogenously applied D‐serine on LTD (Zhang et al, ) or LTP (Yang et al, ) in male rodents.…”
Section: Discussionsupporting
confidence: 56%
“…Importantly, post hoc analysis suggested that such an effect was mostly driven by female mice. While future studies will be necessary to better understand why that might be the case, our observations add additional evidence to the growing body of literature showing a strong sex-dependence of DAAO actions in the rodent brain (Labrie et al, 2009;Pritchett et al, 2015), as well as sex-related differences in its expression levels in humans (Jagannath et al, 2017).…”
Section: Discussionmentioning
confidence: 54%
“…This work fostered development of mGlu2/3 agonists as potential anti-schizophrenia treatments, with a high-profile positive clinical trial for one such drug, pomaglumetad methionil (Patil et al, 2007). Though this finding was not replicated, interest in group II mGluRs in schizophrenia and as antipsychotic drug targets has persisted (Lyon et al, 2011b, Fell et al, 2012, Vinson and Conn, 2012, Lane et al, 2013, Ellaithy et al, 2015, De Filippis et al, 2015, Pritchett et al, 2015, Walker and Conn, 2015), and a recent secondary analysis of the clinical trials suggests that pomaglumetad methionil may have antipsychotic efficacy early in the disease and in patients previously exposed to D2 dopamine antagonists (Kinon et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As proof of principle, Dao knockout ( Dao −/− ) mice have been generated and subjected to tests of cognition. Dao −/− mice exhibit improved spatial and non‐spatial short‐term memory (Pritchett et al ., ), and improved object recognition memory has also been reported in wild‐type (WT) rats following the administration of a DAO inhibitor (Hopkins et al ., ). However, the relationship between DAO function and associative, long‐term spatial memory is less clear.…”
Section: Introductionmentioning
confidence: 88%